Develompent of Softskill Competencies in Writing Student Description Texts Using Learning Model Think Talk Write (TTW) Learning Model for Students of Grade VI - Supurnamawati; Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
The problems in this study are how is the ability to write descriptive text in class VI SD Negeri 104185 Semayang without using the Think Talk Write (TTW) learning model? And how is the development of the ability to write descriptive text in grade VI SD Negeri 104185 Semayang by using the Think Talk Write (TTW) learning model? This research aims to develop the competence of writing description text using Think Talk Write (TTW) learning model in grade VI students of SD Negeri 104185 Semayang. This research is an experimental research (pre-experimental design) with a one group pretest-posttest design using descriptive analysis and inferential statistical analysis conducted four times a meeting. The sample in the study was class VI SD Negeri 104185 Semayang as many as 31 people. The results of the study found two important things, namely. First, the level of ability to write descriptive text without using the Think Talk Write (TTW) learning model for grade VI students of SD Negeri 104185 Semayang obtained an average score of 62.90 with a mastery level of 55-65% with sufficient qualifications. Second, the level of ability to write descriptive text by using the Think Talk Write (TTW) learning model of grade VI students of SD Negeri 104185 Semayang obtained a score of 81.18 with a mastery level of 76%-85% with Good (B) qualifications. It is concluded that the ability to write descriptive texts of grade VI students of SD Negeri 104185 Semayang by using the Think Talk Write (TTW) learning model is better than not using the Think Talk Write (TTW) learning model.